Expression of Concern to: Knockdown of ZFR suppresses cell proliferation and invasion of human pancreatic cancer - Xiaolan Zhao; Man Chen; Jishan Tan (Biological Research, 2018)
Concerns have been raised about this article [1] relating to the appropriateness of the use of the shRNA (5′-GCGGAGGGTTTGAAAGAATATCTCGAGATATTCTTTCAAACCCTCCGCTTTTTT-3′) as a non-targeting control and similarities in text and formatting with other published articles. This is currently under investigation and appropriate editorial action will be taken once the investigation is concluded. The authors did not respond to our correspondence regarding this expression of concern.